Interplay between AHR genotypes, lifestyle factors and adjuvant breast cancer treatments significantly impacts clinical outcome in a population-based cohort - Annelie Augustinsson; Christopher Godina; Linn Nilsson; Kelin Gonçalves de Oliveira; Karolin Isaksson; Helena Jernström (BJC Reports)
Abstract Background The purpose was to evaluate the prognostic impact of aryl hydrocarbon receptor (AHR) genotypes in relation to lifestyle and adjuvant treatments in breast cancer. Methods AHR genotyping was performed on genomic DNA from 1701 patients included 2002–2016 in Lund, Sweden, and followed for up to 15 years. Eight AHR polymorphisms and eight haplotypes were analysed using survival and interaction analyses in relation to prognosis. Results Homozygosity for major allele frequencies was 42.1%–88.5%. AHR genotypes linked to lower AHR expression conferred differential prognosis combined with smoking, alcohol, antioxidant supplements, chemotherapy or endocrine therapy, with interactions between exposures and genotypes. Preoperative antioxidants combined with minor alleles of AHR_6 or AHR_9 conferred three-fold risks for breast cancer events, not seen in other patients (P interactions ≤ 0.016). Interactions between the CGATTAGC haplotype and chemotherapy revealed five-fold risks for breast cancer events or death compared to other haplotypes or no chemotherapy (P interactions ≤ 0.010). AHR genotypes were not prognostic in radiation therapy-treated patients. Conclusions The prognostic impact of AHR genotypes depended on lifestyle and treatments, possibly due to the role of AhR as master regulator of metabolism, hypoxia, DNA repair and immune response. If confirmed, these findings may contribute to more personalised lifestyle recommendations and treatment.